IIEDAD WASAYIL TIKNULUJIA (WTSAB NAMUDHAJA) FI TAELIM ALMUFRADAT LILMUBTADIIYN - Lalu Agus Pujiartha; Muhammad Ghusan Azry; Muhammad Furqan; HeriPurwanto Sidiq (SHAWTUL ARAB, 2024)
Methods and technology play a big role in the educational process, because they are useful for teachers, help them, improve their teaching performance, help teachers to be more precise in targeting the material, evaluate and control it, and help in the educational process to achieve goals. desired goal easily. Vocabulary teaching is important for anyone who wants to learn a second language, for special purposes, for the need to understand books, or to achieve other goals, because vocabulary is an important element of language. This research aims to use WhatsApp as a means of teaching vocabulary, considering that currently the use of this program to communicate with each other is more common, more widely used in the world, and easier to implement. Researchers conducted this research considering the importance of facilities and technology in education as well as the importance of vocabulary in Arabic. Researchers used descriptive analytical methods for this research. This research shows, first, that vocabulary teaching is important. Because vocabulary is an important element of language. Second: Educational methods are one of the important things in the educational process, because they help the learning process to achieve the desired goals easily. Third: WhatsApp can be a means of teaching vocabulary